ISTILAH BERMUATAN BUDAYA DALAM NOVEL SIXTY NINE KARYA RYU MURAKAMI DAN TERJEMAHANNYA TAHUN ENAM SEMBILAN - Adhitya Permana, Gede (Humanis; Volume 10. No 2. Februari 2015)
The focus of discussion in this study are the categories of cultural terms which are found in the novel Sixty Nine by Ryu Murakami and its Indonesian versions Tahun Enam Sembilan and the translation techniques used in translating cultural terms in the novel. The data were qualitatively analyzed using descriptive methods. The steps of data analysis are described as follows: First, categorize the cultural terms by the category proposed by Newmark (1988). Then, the data were analyzed by source language oriented and the target language context technique of translation proposed by Molina and Albir (2002). The categories of cultural term found in Sixty Nine novel are: 1. Ecology (flora, fauna, hills, wind, terrain), 2. Material Culture (food, clothing, housing, urban transport), 3. Social Culture (work, recreation), 4. Organization, Customs, Activities, Procedures, Concepts (Political and Administrative, Religious, Artistic), 5. Gestures and Habits which dominated by material culture categoriy. The applied techniques found in this novel are adaptatation, amplification, borrowing, established equivalent, generalization, literal translation and transposition which dominated by amplification technique.
Keywords: translation, cultural terms, translation techniques